Cellular junction and mesenchymal factors delineate an endometriosis-specific response of endometrial stromal cells to the mesothelium. (1st January 2022) - Lin, Li-Ling; Makwana, Simran; Chen, Meizhen; Wang, Chiou-Miin; Gillette, Laurel H.; Huang, Tim H.; Burney, Richard O.; Nicholson, Bruce J.; Kirma, Nameer B.
Abstract: Endometriosis is a debilitating gynecologic disorder that affects ∼10% of women of reproductive age. Endometriosis is characterized by growth of endometriosis lesions within the abdominal cavity, generally thought to arise from retrograde menstruation of shed endometrial tissue. While the pathophysiology underlying peritoneal endometriosis lesion formation is still unclear, the interaction between invading endometrial tissue and the peritoneal mesothelial lining is an essential step in lesion formation. In this study, we assessed proteomic differences between eutopic endometrial stromal cells (ESCs) from women with and without endometriosis in response to peritoneal mesothelial cell (PMC) exposure, using single-cell cytometry by time-of-flight (CyTOF). Co-cultured primary eutopic ESCs from women with and without endometriosis with an established PMC line were subjected to immunostaining with a panel of Maxpar CyTOF metal-conjugated antibodies (n = 28) targeting cell junction and mesenchymal markers, which are involved in cell-cell adhesions and epithelial-mesenchymal transition. Exposure of the ESCs to PMCs resulted in a drastic shift in cellular expression profiles in ESCs derived from endometriosis, whereas little effect by PMCs was observed in ESCs from non-endometriosis subjects. The transcription factor SNAI1 was consistently repressed by PMC interactions. ESCs from endometriosis patients are unique in that they respond to PMCs by undergoing changes in adhesive properties and mesenchymal characteristics that would facilitate lesion formation. Highlights: Peritoneal mesothelial cells (PMCs) induced a differential mesenchymal response by endometrial cells in endometriosis. Exposure to PMCs induced a hybrid mesenchymal-to-epithelial profile in endometrial stromal cells in endometriosis. SNAI1 was reduced in endometrial stromal cells from women with endometriosis exposed to peritoneal mesothelial cells.